(untitled) (Bangladesh Agronomy Journal, 2019)
An on-farm trial with four orange fleshed sweet potato varieties viz. BARI Mishti Alu-4, BARI Mishti Alu-8, BARI Mishti Alu-12, BARI Mishti Alu-13 including local check (Muli Alu) were evaluated at farming system research and development (FSRD) site, Jalalpur, Sylhet, Bangladesh during rabi season for two consecutive years (2016-2017 & 2017-2018) under Surma‐Kushiyara Floodplain of Bangladesh. The experiment was laid out in a randomized complete block design (RCBD) with six dispersed replications. The results revealed that the genotypes varied considerably in tuber root yields and yield attributing characters. Considering the average tuber root yield performance orange fleshed sweet potato varieties performed better than local variety (Muli Alu). However, among the varieties under studied BARI Mishti Alu-12 produced higher roots yield (40.63 t ha-1) than the other tested varieties. Considering economic return, the highest gross margin (Tk. 5,65,110 ha-1) and benefit cost ratio (5.50:1.00) was also obtained from sweet potato var. BARI Mishti Alu-12 and the lowest returnfrom var. BARI Mishti Alu-4 with benefit cost ratio of 3.54. Though the local cultivar (Muli Alu) produced lower root yields but it provided considerable gross margin (Tk.3,76,240 )and BCR (3.99:1.00 ) which closed to BARI Mishti Alu-12. It is due to higher demand of local cultivar with high price in the local market. Therefore, the genotypes BARI Mishti Alu-12 and local cultivar (Muli Alu) were found suitable for their better growth and yield under the acidic soils Bangladesh Agron. J. 2018, 21(2): 59-65